Influence of static Jahn-Teller distortion on the magnetic excitation spectrum of PrO2: A synchrotron x-ray and neutron inelastic scattering study - Webster, C; Helme, L; Boothroyd, A; McMorrow, D; Wilkins, S; Detlefs, C; Detlefs, B; Bewley, R; McKelvy, M (2007)
A synchrotron x-ray diffraction study of the crystallographic structure of PrO2 in the Jahn-Teller distorted phase is reported. The distortion of the oxygen sublattice, which was previously ambiguous, is shown to be a chiral structure in which neighbouring oxygen chains have opposite chiralities. A temperature dependent study of the magnetic excitation spectrum, probed by neutron inelastic scattering, is also reported. Changes in the energies and relative intensities of the crystal field transitions provide an insight into the interplay between the static and dynamic Jahn-Teller effects.